Why mixing alcohol, opioids and benzodiazepines can kill. Issue 6 (7th February 2020) - Knopf, Alison
Abstract : Alcohol, opioids and benzodiazepines are very different pharmacologically but have similar effects in the brain when it comes to reinforcement — and also to respiratory depression and death.